Enhanced properties of TEMPO-oxidized bacterial cellulose films via eco-friendly non-pressurized hot water vapor treatment for sustainable and smart food packaging - Rahmadiawan, Dieter; Abral, Hairul; Azka, Muhammad Adlan; Sapuan, S.M.; Admi, Ratna Isnanita; Shi, Shih-Chen; Zainul, Rahadian; Azril, None; Zikri, Ahmad; Mahardika, Melbi (Royal Society of Chemistry, 2024)
Developing a simple and environmentally friendly method to vary the physical, mechanical, and thermal properties of cellulose films is of great importance. This study aimed to characterize 2,2,6,6-tetramethylpiperidinyl-1-oxyl (TEMPO)-oxidized bacterial cellulose (BC) films prepared using non-pressurized hot water vapor (NPHWV) method. A wet BC-pellicle that had been oxidized with TEMPO was treated with NPHWV for 60, 120, and 240 minutes, respectively. As a control, a TEMPO-oxidized BC (TOBC) film without NPHWV was prepared. The results show that the longer NPHWV duration of the TOBC film increased the tensile and thermal properties. This film became more hydrophobic and showed lower moisture absorption, thermal conductivity and organic solvent uptake, more crystalline structure, and higher fiber density after NPHWV treatment. The acquired results provide a simple, inexpensive, and ecologically friendly method for varying TOBC film properties.